Study Of Bi-Functionalized Laterite Soil In Treating Dye Wastewater Through Coagulation-Flocculation And Degradation - Lau, Yen Yie (2015)
Raw laterite soil collected from Bukit Merah, Perlis, Malaysia went through decolorization pre-treatment before being used as coagulant-flocculant. This key material is dominated by silica component (36.30 %), followed by aluminum (27.10 %) and ferric (26.86 %). Silica was activated at the acidic region (pH 2) which allowed the silica to cleave the dye molecular structure through suhstituition, electrical douhle layer compression and charge neutralization. Meanwhile, aluminium and ferric act as auxiliary agents in the coagulation-flocculation process. Laterite soil was able to remove: acid orange 7 with 99.50 % at dosage of 14000 mg/L; methylene blue with 99.61 % at dosage of2500 mg/L; methyl orange with 99.11 % at dosage of9000 mgII " cibacron brilliant yellow 3G-P with 99.46 % at dosage of 8000 mgfL and reactive red 120 with 99.53 % at dosage of 6000 mgIL. This project has provided a new insight into an effective dye degradation using a new class of natural coagulant-flocculantnatural resources.